"A gutenberg moment": The do‐it‐yourself world of online literary publishing. Issue 1 (2015) - Fleming‐May, Rachel A.; Green, Harriett
ABSTRACT: The Internet has changed the publishing industry irrevocably; this phenomenon has affected the print‐centric sphere of literary publishing as well as those fields that have typically accepted change more readily. This poster presents findings from a study of the opinions and practices of editors and publishers of literary journals published online either in part or exclusively. In a survey and follow‐up interviews, we asked respondents to describe the benefits and drawbacks of publishing literature using web‐based platforms as well as their perceptions of the larger impact online publishing is having on literature. This study represents a unique attempt to explore the creative field of literature through the theoretical lens of information science.